PERAN STRATEGIS GURU DALAM PENGEMBANGAN KURIKULUMPENDIDIKAN AGAMA ISLAM DI ERA KURIKULUM MERDEKA - Nailul Muna Nailul Muna; Ibnu Nazif; Sumiarti; Muhammad Fauzan (Jurnal Pendidikan Nusantara, 2026)
Teachers are the key component that determines the success of curriculum implementation in educational units. This study aims to examine in depth the role dimensions of Islamic Religious Education (PAI) teachers in the context of curriculum development, particularly in three main capacities: as instructional designers, implementers, and evaluators. Furthermore, this article analyzes the demands for behavioral transformation of PAI teachers in line with the implementation of the Merdeka Curriculum as the latest educational policy. Through a literature review approach drawing on various empirical studies and relevant scientific sources, it is found that PAI teachers carry four fundamental roles, namely as curriculum implementors, adaptors, developers, and researchers. The Merdeka Curriculum calls for a paradigm shift from teacher-centered to student-centered learning, accompanied by enhanced digital literacy competencies and the application of differentiated learning strategies. However, various obstacles remain in this transition process, ranging from limited conceptual understanding to resistance against changing teaching habits. Therefore, comprehensive systemic support from various stakeholders is needed to optimize the role of PAI teachers in realizing holistic Islamic educational goals.